Absorbing a Little Water: The Structural, Thermodynamic, and Kinetic Relationship between Pyrogallol and Its Tetarto-Hydrate - Braun, Doris E. (American Chemical Society, 2013)
[Image: see text] The anhydrate and the stoichiometric tetarto-hydrate of pyrogallol (0.25 mol water per mol pyrogallol) are both storage stable at ambient conditions, provided that they are phase pure, with the system being at equilibrium at a(w) (water activity) = 0.15 at 25 °C. Structures have been derived from single crystal and powder X-ray diffraction data for the anhydrate and hydrate, respectively. It is notable that the tetarto-hydrate forms a tetragonal structure with water in channels, a framework that although stabilized by water, is found as a higher energy structure on a computationally generated crystal energy landscape, which has the anhydrate crystal structure as the most stable form. Thus, a combination of slurry experiments, X-ray diffraction, spectroscopy, moisture (de)sorption, and thermo-analytical methods with the computationally generated crystal energy landscape and lattice energy calculations provides a consistent picture of the finely balanced hydration behavior of pyrogallol. In addition, two monotropically related dimethyl sulfoxide monosolvates were found in the accompanying solid form screen.